Synchronous ectopic gastric mucosa in an infant with Meckel′s diverticulum and lower gastrointestinal bleed - Sharma S; Debnath P; Tripathi R; Mishra A; Deori P; Agrawal L (Wolters Kluwer Medknow Publications, 2007)
A 7-months-old male child presented with severe lower gastrointestinal bleeding. His radionuclide scan showed ectopic gastric mucosa in Meckel′s diverticulum as well as in distal ileum. On exploration a 5 cm indurated bleeding ulcer found in ileum but no ulcer in Meckel′s diverticulum or adjacent ileum. Histopathological examination of the specimen confirmed the diagnosis of ectopic gastric mucosa in ileum causing bleeding ulcer. Resection of the segment with end-to-end anastomosis cured the child. Such a synchronous lesion with Meckel′s diverticulum has the potential to be missed, unless careful evaluation is done.